Análise do polimorfismo R577X do gene alfa actina 3 como possível preditor de desempenho físico em mulheres ultramaratonistas - Zonatto, Hiago Augusto (2018)
The elite athletic performance is a result of environmental and genetic factors. The genetic component seems to explain the better training adaptation some individuals show over others, making possible to estimate ideal morphophysiological characteristics for a specific sports modality. One of the genes that can have an effect on the human athletic performance is the α-actin-3 (ACTN3), heavily researched due to its important structural function in the skeletal muscle, in addition to its possible influence over the physical capacities of power/strength and muscle resistency. The aim of this research was to verify the occurrence of the genetic polymorphism R577X of the gene ACTN3 in ultra-endurance athletes. The research sample was composed of 19 female Brazilian elite ultra-endurance runners with national and international experience in the category and average age of 41,2 ± 6,1 years. The R577X ACTN3 polymorphism genotyping was performed by the Polymerase Chain Reaction (PCR), with extracted DNA from saliva, whereas the body composition was measured by bioimpedance analysis. The genotypic and allelic frequencies were analysed and compared with data from the control group by the following tests: Hardy-Weinberg equilibrium, Pearsons Chi-Square, Yates correction Chi-Square, and the data regarding the lean mass and fat mass component were statistically analysed by the Kruskal-Wallis test, considering p≤0,05 as the value for statistical significance for all of the tests performed. The results have shown a higher frequency of the RX and XX genotypes for the athletes compared to the control group, although the difference is not significant (RR=15,8%, RX=57,9%, XX=26,3% versus RR=40%, RX=46%, XX=14%). Regarding the allelic distribution, it was observed a higher appearance of the non-functional allele on the studied group when compared with the control group (R=44,7%, X=55,3% versus R=63%, X=37%), with a significant difference (p-value=0.0350). Concerning the body composition it wasn’t observed differences among the genotypes, considering that the mean lean mass for athletes on the group RR was 86%, RX=85,31% and XX=86,56%. In conclusion, the data reported in this research shows a correlation between the X allele from the ACTN3 gene and the athletic condition of female brazilian ultramarathoners, however it was not noted an influence of the R577X polymorphism over the athlete’s body composition.